Print media study on communicate misleading information by tobacco industry - Achala Dilrukshi (Tobacco Induced Diseases, 2018)
Background and challenges to implementation Objectives of this study are to; identify the new tactics of Ceylon Tobacco Company(CTC) making fabrications through media in order to decelerate the implementation of tobacco tax policies. It is proven that one of best sustainable tobacco control method is to hike cigarettes tax which reduces cigarette consumption. 2016, Sri Lankan government increased cigarettes tax thrice as never done before. CTC tried to demolish this effort by fabricating as they done before.